درجة معرفة معلمي التربية الخاصة بخصائص الأطفال ذوي اضطراب طيف التوحد وعلاقتها بأساليب التعامل معهم - نوافلة , وسام هاني (Scientific Journal of University of Benghazi, 2023)
The study aimed to identify the extent to which special education teachers know about the characteristics of children and methods of dealing with children with autism spectrum disorder, and to reveal the nature of the relationship between the knowledge of children with autism spectrum disorder and the methods of dealing with them. Finding differences between special education teachers' approaches to children with autism spectrum disorder depending on the variable (years of experience). The study sample consisted of 127 teachers working in special education schools and centres in Jordan. The sample was selected at random. To achieve the objectives of the study, a questionnaire was applied on the knowledge of special education teachers about the characteristics of children with autism spectrum disorder, and a questionnaire on the knowledge of special education teachers about the methods of dealing with children with autism spectrum disorder, developed by the researcher for the purposes of the current study. The results showed that the degree of knowledge among special education teachers of the characteristics of children with autism spectrum disorder as a whole was (high), as was first after "social communication and social interaction", and second after "stereotypes". The degree of knowledge among special education teachers of the methods of dealing with children with autism spectrum disorder as a whole was high, as was the first place after "enhancement methods and strategies" to a high degree, the second place after "individual training methods and strategies" to a high degree, and the last place after "varied training methods and strategies" to a high degree. It also showed a positive statistically significant correlation between educators' knowledge of the characteristics of children with autism spectrum disorder and their handling methods. There are no statistically significant differences attributable to the impact of the number of years' experience.